Assessing the Impacts of Income and Price Shocks on Food Security and Diets: The Food Security Simulator, Nigeria (FSSN) - CGIAR; Onilogbo, Omobolanle (CGIAR System Organization, 2023)
On August 17, IFPRI Nigeria under the CGIAR Initiative on National Policies and Strategies (NPS) facilitated a seminar to make a presentation on “Assessing the Impacts of Income and Price Shocks on Food Security and Diets: The Food Security Simulator, Nigeria (FSSN)” in collaboration with the National Bureau of Statistics (NBS).